2019
DOI: 10.2134/agronj2018.07.0462
|View full text |Cite
|
Sign up to set email alerts
|

World Potassium Use Efficiency in Cereal Crops

Abstract: Core Ideas Potassium use efficiency in cereals is unknown. World demand for potassium in agriculture is increasing. Potassium is a non‐renewable resource. Worldwide potassium (K) fertilizer use has grown, while the expected fertilizer use efficiency has decreased. The objective of this paper was to estimate potassium use efficiency (KUE) for cereal crops and report on methods that will most likely lead to improved KUE. World KUE was calculated using the total area under cereal production, total cereal grain p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 57 publications
0
66
1
1
Order By: Relevance
“…Procedures and assumptions made in work done by Raun and Johnson (1999), Dhillon et al (2017), and Dhillon et al (2019a) to compute NUE, PUE, and KUE, respectively, were used to determine SUE for major world cereal crops. It is important to note that this study did not investigate agronomic efficiency and partial productivity factor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures and assumptions made in work done by Raun and Johnson (1999), Dhillon et al (2017), and Dhillon et al (2019a) to compute NUE, PUE, and KUE, respectively, were used to determine SUE for major world cereal crops. It is important to note that this study did not investigate agronomic efficiency and partial productivity factor.…”
Section: Methodsmentioning
confidence: 99%
“…This low SUE together with 33% nitrogen use efficiency (NUE) (Raun and Johnson, 1999), 16% phosphorus use efficiency (PUE) (Dhillon et al, 2017), and 19% potassium use efficiency (KUE) (Dhillon et al, 2019a) for a range of cereals, represents an inefficient use of these macronutrients. With S linked to improved efficiency of N recovery in the grain (NUE), its use in crop production will only continue to grow (Klikocka et al, 2017).…”
mentioning
confidence: 99%
“…The impact of other basic nutrients on the productivity of this crop, including potassium (K) and magnesium (Mg) is, in fact, a black box. As recently published by Dhillon et al [12], K use efficiency in cereals is low, amounting to 19%. The physiological functions of K as related to water management by crop plants are well recognized.…”
Section: Introductionmentioning
confidence: 85%
“…Phosphorus use efficiency in cereal crops was found to be 16% on average over a 53‐yr period (range, 12–21%) (Dhillon et al, 2017). Similarly, over a 55‐yr period, potassium use efficiency averaged 19% (range, 15–26%) (Dhillon et al, 2019). Likewise, sulfur use efficiency averaged 18% (range, 14–22%) (Aula et al, 2019).…”
Section: Entropy and Randomnessmentioning
confidence: 96%
“…Global estimates of phosphorus (P) (Dhillon et al, 2017), potassium (K) (Dhillon et al, 2019), and sulfur (S) (Aula et al, 2019) use efficiencies in cereal crops have been found to be highly variable from one year to the next. Phosphorus use efficiency in cereal crops was found to be 16% on average over a 53‐yr period (range, 12–21%) (Dhillon et al, 2017).…”
Section: Entropy and Randomnessmentioning
confidence: 99%